A Causal Model of the Mutual Relationships Between Academic Bullying, Suicidal Thinking, and Psychological Immunity Among University Students - Hassan, Amani Abdel-Tawab Saleh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to identify the causal model that explains the relationship between academic bullying, psychological immunity, and suicidal thinking among university students. Besides, it recognizes gender differences in research variables. The sample has consisted of (134) male and (139) female students from Prince Sattam bin Abdul-Aziz University and King Faisal University for the academic year 2020-2021. The researcher prepared the academic bullying scale and the suicidal thinking scale, and the psychological immunity scale was taken from the study of Al-Takhaina. The study has shown a statistically significant correlation between academic bullying and suicidal thinking. There are statistically significant differences between males and females in academic bullying and suicidal thinking favoring females. The results have also shown statistically significant differences between males and females in psychological immunity favoring males. The research recommends launching counseling and training programs for both bullies and bullying victims to gain insight into their behaviors and rectify them.